A systematic review of steroid use in peripheral nerve pathologies and treatment - Couch, Brandon; Hayward, Dan; Baum, Gracie; Sakthiyendran, Naveen Arunachalam; Harder, Justin; Hernandez, Evan J.; MacKay, Brendan (Frontiers in Neurology, 2024)
Background The use of corticosteroids has become a part of the standard of care in various pathologies but their use in peripheral nerve injury treatment is limited. Given corticosteroids’ anti-inflammatory properties and their regulatory role in neuronal protein production and myelination, corticosteroids could serve as an adjunct therapy for peripheral nerve injuries. This review aims to systematically investigate the current use of corticosteroid treatment in peripheral nerve pathologies. Methods The systematic search was performed on PubMed, MEDLINE, EMBASE, Scopus, Cochrane, and Web of Science using keywords such as “corticosteroid treatment,” “peripheral nerve damage,” “peripheral neuropathy,” and “complications.” The PRISMA guidelines were used to conduct the systematic review and all articles were reviewed by the corresponding author. After the initial search, individual study titles and abstracts were further screened and categorized using an inclusion and exclusion criteria followed by a final full-text review. Results Out of the total 27,922 identified records, 203 studies were included based on the selection criteria. These studies focused on the use and efficacy of steroids across a spectrum of compression and non-compression peripheral neuropathies such as cubital tunnel syndrome and chronic inflammatory demyelinating polyradiculoneuropathy. Various studies noted the promising role of steroids in offering pain relief, nerve block, and nerve regeneration effects. Additionally, safety considerations and potential complications regarding steroid use in peripheral nerve injuries were analyzed. Conclusion While there is currently limited clinical utilization of corticosteroids in peripheral nerve pathologies, the anti-inflammatory and regenerative effects that steroids provide may be a beneficial tool in managing various peripheral neuropathies and their associated pain. Additional clinical trials and investigation into the mechanism of action could improve the reputation of steroid use as peripheral nerve injury treatment.